Isolasi dan Uji Aktivitas Antimikroba Ekstrak Daun Tumbuhan Jatropha Multifida L (Jurnal Pilar Sains, 2006)
Have been studied biologis activity test and sitotoxic test of jatropha multida leaf extract . Extractionhave been done with heksane, ethyl acetate and methanol. Activity test with diffusion methode andsitotoxic test with Brine Shrimp Lethality Test method use Artemia salina species.Heksane exstract obtained 2 pure compounds, Jm 1 with meldng point 73-75 °C and 3m 2 withmelting point 163-164 °C. Extract etylacetate and methanol have been yet obtained pure compound.Biologis activity test showed all of extract negatif to micro organisme test. Sitotoxic test showedmethanol and hexane extract negative to anemia sauna species and ethyl acetate extract have beencharacter of toxic to Anemia sauna species at the price of LC5O =52 ppm.